DETERMINATION OF THE STRUCTURE OF THE MONOLAYER OF HEXADECYLTRIMETHYL AMMONIUM BROMIDE ADSORBED AT THE AIR-WATER-INTERFACE - Lu, J; Hromadova, M; Simister, E; Thomas, R; Penfold, J (Elsevier, 1994)
We have studied the adsorption of hexadecyltrimethyl ammonium bromide (C16TAB) at the air-water interface at its CMC using the neutron reflection technique. The reflectivity profiles have been analysed using both a layer model with the optical matrix method and a recently developed approach based on the kinematic approximation. Assuming a uniform layer distribution for the fragments comprising the layer, the total thickness of the monolayer is found to be 21 ± 2 A, of which 10 A is immersed in water. The shapes and widths of the distributions of the alkyl chain, head and water are compared with those from a recent computer simulation of hexadecyltrimethyl ammonium chloride (C16TACl). Good agreement is obtained for the distances between the centres of the three distributions.